2005
DOI: 10.1086/498619
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Scan and Fine-Mapping Linkage Studies in Four European Samples with Bipolar Affective Disorder Suggest a New Susceptibility Locus on Chromosome 1p35-p36 and Provides Further Evidence of Loci on Chromosome 4q31 and 6q24

Abstract: We present the findings of a large linkage study of bipolar affective disorder (BPAD) that involved genomewide analysis of 52 families (448 genotyped individuals) of Spanish, Romany, and Bulgarian descent and further fine mapping of the 1p34-p36, 4q28-q31, and 6q15-q24 regions. An additional sample of 56 German families (280 individuals) was included for this fine-mapping step. The highest nonparametric linkage scores obtained in the fine mapping were 5.49 for 4q31 and 4.87 for 6q24 in the Romany families and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 32 publications
1
64
2
Order By: Relevance
“…21,22 As mentioned in the introduction, the GluR6 gene is located on chromosome 6q21, a region reported by several groups to be linked with BPD. [6][7][8][9] Moreover, it has recently been shown that cortical expression levels of GluR6 are lower in the cortex of BPD patients. 10 Mania traditionally manifests as severe mood elevation (either euphoria or irritability) and is accompanied by behavioral excitement, including hyperactivity and psychomotor agitation, an increase…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,22 As mentioned in the introduction, the GluR6 gene is located on chromosome 6q21, a region reported by several groups to be linked with BPD. [6][7][8][9] Moreover, it has recently been shown that cortical expression levels of GluR6 are lower in the cortex of BPD patients. 10 Mania traditionally manifests as severe mood elevation (either euphoria or irritability) and is accompanied by behavioral excitement, including hyperactivity and psychomotor agitation, an increase…”
Section: Discussionmentioning
confidence: 99%
“…5 Genetic linkage of BPD to chromosome 6q21 has been demonstrated in several studies, and genome-wide significant linkage was recently established by meta-analysis. [6][7][8][9] Buervenich and colleagues investigated the broad linkage peak on 6q and found that a specific haplotype, located on the regulatory region of the human GluR6 gene, was associated with BPD. In addition, very recent post-mortem studies demonstrate a reduction in GluR6 mRNA levels in the brains of BPD patients, 10 thus pointing to GluR6 as a potential candidate gene in the pathophysiology of BPD.…”
Section: Introductionmentioning
confidence: 99%
“…BPI, BPII and MDE are defined as distinct entities in DSM-IV, which allows a high inter-rater concordance but which was not constructed to distinguish between different clinical entities depending on distinct genetic factors. Most genome-wide linkage scans have analyzed broad, intermediate and narrow phenotypes using a gradient from MDE to BPI through BPII (Garner et al, 2001;McInnis et al, 2003;Fallin et al, 2004;Schumacher et al, 2005;Zandi et al, 2007, Vazza et al, 2007Nwulia et al, 2007;Venken et al, 2007). This phenotypic classification may not be the most appropriate for defining phenotypes for the identification of linkage regions.…”
Section: Discussionmentioning
confidence: 99%
“…5 The problem of population stratification has led most investigators to confine their study populations to Caucasians, 6 or even more narrowly to Caucasians of European descent. 7,8 This approach does not necessarily mitigate the effects of population stratification, as it fails to account for genetic subcategories within groups commonly considered 'Caucasian'. 9 Moreover, it is also possible that these very differences in genetic profiles in different ethnic groups explain, in part, the different observed prevalence rates for psychiatric disorders across ethnic groups.…”
Section: Ethnicity and Genesmentioning
confidence: 99%